Integrated Application of Iso-Seq and RNA-Seq Analyses to Uncover Genes Involved in Ovarian Development in Platypharodon extremus - Zhuoyu Yang; Yanping Zhang; Wei Ka; Wenjing He; Yujie Yang; Wenlong Jiao; Jianlin Wang (Fishes, 2026)
This study focused on Platypharodon extremus, a species endemic to the Qinghai–Tibet Plateau, and systematically analyzed its reproductive biology, sex steroid hormones, ovarian histology, and transcriptomic characteristics throughout its complete reproductive cycle (August 2020 to June 2021). The results demonstrated that the body length, height, body weight, and gonadal weight of female individuals continuously increased with age, while the Gonadosomatic index (GSI) was lowest during the breeding season (June–August) and gradually rose during the non-breeding period. Serum estradiol (E2) and progesterone (P4) exhibited rhythmic fluctuations corresponding to ovarian development: E2 rose from 25.77 ng/L in stage-I to 146.00 ng/L in stage-V, then declined post-ovulation; P4 increased from 59.88 pmol/L in stage-I to 239.03 pmol/L in stage-V, showing a significant decrease after ovulation. Histological observations classified ovarian development into stages I–VI, clearly delineating the complete process from oogonium proliferation, cortical vesicle formation, yolk accumulation, maturation to postpartum regression. To explore molecular changes during the transition from vitellogenesis to oocyte maturation, we built a reference transcriptome with 30,060 non-redundant transcripts (average length = 1975 bp) using PacBio and Illumina data, and 91.87% of these transcripts received functional annotation hits against public databases. A comparative differential expression analysis was performed between ovarian stage III (active yolk accumulation) and stage V (oocyte fully matured). A total of 11,324 differentially expressed genes were identified (5249 upregulated and 6175 downregulated) between these two stages. GO enrichment analysis revealed predominant involvement in cellular processes, cellular components, and catalytic activities, while KEGG analysis demonstrated significant enrichment in metabolic pathways, PI3K-Akt, MAPK, and calcium signaling pathways. Quantitative PCR (qPCR) validation confirmed that candidate genes, including pik3a, calm, mapk1 map2k ddx49, and igf2 were significantly upregulated at stage V. These differentially expressed genes (DEGs) may represent potential molecular signatures linked to the transition from vitellogenesis to oocyte maturation. Our integrated transcriptomic and qPCR data identify potential gene candidates involved in ovarian maturation; however, these findings reveal correlation rather than direct regulatory causality. This study offers fundamental data and theoretical insights for understanding the reproductive regulatory mechanisms and aquaculture management of this endemic species.